Perbedaaan prinsip operasional bank konvensional dan syariah - Nabila, Adinda Tasya; Chotimah, R.A. Meidi Chusnul (Maliki Interdisciplinary Journal, 2024)
The purpose of writing this article is to be useful for readers regarding information on Conventional Banks and Sharia Banks, it is revealed that both have different operational principles. Conventional banks are oriented towards financial profits by using an interest system in transactions, while Sharia banks operate based on the principles of justice, blessings and compliance with Islamic sharia law without using interest. In addition, conventional banks offer interest-based products and services such as loans and deposits, while sharia banks provide products based on sharia principles such as murabahah and mudharabah financing. The method for obtaining data and information is by literature review. So, the research results obtained are that conventional banks can invest in various sectors, including those considered haram in Islam, while sharia banks can only invest in halal businesses. These differences reflect different approaches in achieving operational and investment objectives between the two types of banks.